Complex indirect effects of epiphytic bromeliads on the invertebrate food webs of their support tree. (18th June 2019) - Rogy, Pierre; Hammill, Edd; Srivastava, Diane S.
Abstract: Ecosystem engineers are species that affect others through the provision of habitat rather than consumptive resources. The extent to which ecosystem engineers can indirectly affect entire food webs, however, is poorly understood. Epiphytic tank bromeliads (Bromeliaceae) are ecosystem engineers that are common throughout the Neotropics, and are associated with a variety of predatory arthropods. Here, we examine if bromeliads, by increasing predator densities, indirectly benefit their support tree through reduction in herbivorous insects and leaf damage. We observed and manipulated bromeliad densities in Costa Rican orange orchards, and measured impacts on leaf damage and arboreal and bromeliad invertebrate communities in two different seasons. Our results show that bromeliads are associated with predatory and herbivorous invertebrates but not leaf damage. Bromeliads were correlated with increased densities of their associated predators, especially ants and hunting spiders, but we could not confirm a causal link. Associations with bromeliads changed over time, with seasonal shifts interfering with responses to our manipulations. Bromeliads had a reduced association with predators in the dry season. Moreover, a null association between bromeliads and herbivorous invertebrates in the dry season unexpectedly became positive in the wet season. In summary, we have only limited evidence that bromeliads indirectly promote the top‐down control of arboreal herbivores; instead, our manipulations suggest that bromeliads increase herbivore densities in the wet season. This research suggests that although bromeliads may act as ecosystem engineers, indirectly influencing the invertebrate food web on support trees, their effects are trophically complex and seasonally dependent. Abstract in Spanish is available with online material. Resumen: Los ingenieros de ecosistemas afectan otras especies a través del suministro de hábitat más que suministrando recursos. Sin embargo, poco se sabe sobre el efecto indirecto de dichos ingenieros en la totalidad de redes tróficas. Las bromelias epífitas (Bromeliaceae) son ingenieras de ecosistemas comunes de la zona neotropical, y se asocian con diversas especies de artrópodos depredadores. En este estudio, examinamos si las bromelias benefician indirectamente a sus forófitos por el aumento de las densidades de depredadores y por ende, la disminución de insectos herbívoros y daños foliares. Manipulamos las densidades de bromelias en fincas de naranja en Costa Rica, y estimamos el impacto a los daños foliares, las comunidades de invertebrados de los árboles y de las bromelias, durante una temporada seca y una lluviosa. Nuestros resultados demuestran que las bromelias, no afectaron los daños foliares pero si impactaron a los invertebrados. Encontramos una correlación positiva entre la densidad de depredadores asociados, particularmente hormigas y arañas cazadoras y la presencia de las bromelias. Sin embargo, no pudimos confirmar causalidad. Dichos efectos varían con la temporada. Las bromelias muestran una asociación reducida con depredadores en la temporada seca. Además, una asociación nula entre bromelias y herbívoros en la temporada seca fue positiva en la temporada lluviosa. En conclusión, nuestro estudio provee evidencia parcial de que las bromelias promueven un control trófico en sus forófitos. Nuestros resultados sugieren que bromelias incrementan herbívoros en la temporada lluviosa. Además, sugieren que las bromelias modifican los ecosistemas contiguos, de forma compleja y de temporada.